PENERAPAN MODEL PEMBELAJARAN TIM AHLI DALAM MENINGKATKAN KREATIVITAS SISWA DAN HASIL BELAJAR METABOLISME - Patekur, Patekur (JPB - Jurnal Pendidikan Biologi, 2021)
This study aimed to describe the increase in student creativity and to determine the increase in learning outcomes of metabolic material through the application of the expert team cooperative learning model. This research was a classroom action research and a descriptive quantitative research method. The study was conducted in two cycles with the stages of research according to Kammis and Mc. Taggart, which is in the form of a spiral cycle consisting of four steps, namely planning, implementing the action, observing, and reflecting. The object of this research was 33 students of XII MIPA 3 at SMAN 1 Paciran which consisted of 7 boys and 26 girls. The research instruments used observation sheets to determine student creativity and learning test sheets to determine student learning outcomes. The results of this research and data analysis indicate that the application of the cooperative model of the expert team can increased student learning creativity in learning metabolism, 51.51% -75.75% in cycle I increases to 82.82% -93.94% in cycle II for all indicators become very good and good qualifications. Student learning outcomes on metabolic material have increased with the application of expert team learning. First, the increased in the number of students who achieved target was shown from 15 students in cycle I to 29 students in cycle II. Second, the increased in the average score of students from 62.5 in cycle I to 75, cycle II. Third, the increased in classical completeness from 45.45% in the first cycle to 87.88% in the second cycle. So it can be concluded that the application of the expert team learning model can increase student creativity and student learning outcomes on metabolic material in class XII MIPA 3 SMAN 1 Paciran.